A modified equally sloped algorithm based on the total variation algorithm in computed tomography for insufficient data. (16th February 2017) - Wang, Lei; Guan, Yong; Liang, Zhiting; Guo, Liang; Wei, Chenxi; Luo, Ronghui; Liu, Gang; Tian, Yangchao
Abstract : A modified equally sloped reconstruction algorithm has been proposed, which can achieve high‐quality reconstructions from projections with limited‐angle, few‐view and noisy data. Abstract : Computed tomography (CT) has become an important technique for analyzing the inner structures of material, biological and energy fields. However, there are often challenges in the practical application of CT due to insufficient data. For example, the maximum rotation angle of the sample stage is limited by sample space or image reconstruction from the limited number of views required to reduce the X‐ray dose delivered to the sample. Therefore, it is difficult to acquire CT images with complete data. In this work, an iterative reconstruction algorithm based on the minimization of the image total variation (TV) has been utilized to develop equally sloped tomography (EST), and the reconstruction was carried out from limited‐angle, few‐view and noisy data. A synchrotron CT experiment on hydroxyapatite was also carried out to demonstrate the ability of the TV‐EST algorithm. The results indicated that the new TV‐EST algorithm was capable of achieving high‐quality reconstructions from projections with insufficient data.